Hurler’s Syndrome - A Case Report (Mucopolysaccharidosis Type-1H) - Islam, AHM Tohurul; Leema, Elora A; Das, Tapos K; Ali, O Ibne; Rahman, MH; Nahar, Z (TAJ: Journal of Teachers Association, 2018)
A girl named Tania, aged 5yrs was brought to Shaheed Ziaur Rahman Medical College Hospital, Bogra with the complains of swelling of both legs for 5days & low grade intermittent fever for 1month & she also had severe mental retardation, facial dysmorphism, hepatosplenomegaly, umbilical hernia, corneal clouding, large calvaria & features of dysostosis multiplex. Her clinical as well as radiological features arouse strong suspicion suffering from a rare genetic disease (autosomal recessive) hurler’s syndrome though it wasn’t confirmed by deficiency of specific enzyme or urinary excretion of GAG (glycosaminoglycan). TAJ 2011; 24(2): 148-151